Les contraintes du milieu et la gestion de la politique étrangère canadienne de 1976 à 1978 - Kirton, John (Études internationales, 1979)
The direction and pace of efforts to co-ordinate the foreign policy making process within the executive branch of middle-size states may depend on subtle but cumulatively important shiefs in domestic and external environments. The experience of the Canadian government from 1976 to 1978 suggests the effects which four types of environmental change can have. The approach of a federal election was accompanied by a reduced emphasis on the formal procedures of the structured cabinet committee System instituted in the early years of the first Trudeau government. An increased threat to national unity, as registered in the November 1976 election of a Parti Québécois majority provincial government, concentrated decisional activity at the very centre of government, and had only indirect effects on the formal foreign policy planning process. Concern with persistent economic dilemmas, registered most clearly in the imposition of an expenditure restraint programme in August 1978, directly increased the use of the budgetary process and prompted moves toward foreign service integration. And the intensification of a decline in tension in relations with the United States, and the accompanying emergence of new global problems, led, in turn, to a transfer of dynamic, creative co-ordinatively-oriented leadership into the Department of External Affairs, a reorganization of the Department, and a strong stress on re-orienting its role toward that of a modem central policy agency.